Wacana Fikih Kebangsaan dalam Penanggulangan dan Pencegahan Radikalisme di Lingkungan Kampus di NTB - Masnun Tahir (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2015)
Islamic militant group is arguably followed by laymen circle is. Change of movementis condusted by this group. This group tries to gain support from university students as a new agent which is assumed by this group to be able to change movement pattern. Spreading of Islamic radical group in the area of student is not apart from striving for caderization of intllectual group in Islamic fundamentalist circle. This strategy is an indoctrination of ideology which caused student feels difficult to cut his relation to this group. This phenomenon finally forms a new metamorphosis to a new Islamic radical movement in campus.